Proceedings of the Fifth International Conference on Animal-Computer Interaction 2018
DOI: 10.1145/3295598.3314845
|View full text |Cite
|
Sign up to set email alerts
|

SoundJam 2018

Abstract: This workshop is designed to offer participants an opportunity to explore different kinds of auditory enrichment for a range of animals in different environments. Teams of participants will work together on a small set of briefs provided by domain experts, brainstorming ideas and developing concepts into welldesigned blueprints for prototype devices. The day will be organized along the lines of a traditional gamejam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…French's work on interactive auditory enrichment for African elephants (French et al, 2018a) uses a physical trigger to provide control to the animal. The "Sound Jam" workshop (French et al, 2018b) also demonstrated momentum within the field of Animal-Computer Interactions (ACI) to create interactive auditory enrichment systems. Further motivating the need for interactiveness, Ritvo (2013) found that there may be differences in how orangutans and humans experience music.…”
Section: Sonic Enrichmentmentioning
confidence: 99%
“…French's work on interactive auditory enrichment for African elephants (French et al, 2018a) uses a physical trigger to provide control to the animal. The "Sound Jam" workshop (French et al, 2018b) also demonstrated momentum within the field of Animal-Computer Interactions (ACI) to create interactive auditory enrichment systems. Further motivating the need for interactiveness, Ritvo (2013) found that there may be differences in how orangutans and humans experience music.…”
Section: Sonic Enrichmentmentioning
confidence: 99%
“…In 2017, the FarmJam focused on environmental enrichment for intensively farmed animals [7] (pigs, goats and chickens) and the associated challenges. In 2018, the SoundJam addressed opportunities for auditory enrichment for animals in a range of captive contexts [9] (chimpanzees, parrots, servals and elephants).…”
Section: Introductionmentioning
confidence: 99%